2009
DOI: 10.1074/jbc.m109.052720
|View full text |Cite
|
Sign up to set email alerts
|

A Truncated Form of p23 Down-regulates Telomerase Activity via Disruption of Hsp90 Function

Abstract: The Hsp90-associated protein p23 modulates Hsp90 activity during the final stages of the chaperone pathway to facilitate maturation of client proteins. Previous reports indicate that p23 cleavage induced by caspases during cell death triggers destabilization of client proteins. However, the specific role of truncated p23 (⌬p23) in this process and the underlying mechanisms remain to be determined. One such client protein, hTERT, is a telomerase catalytic subunit regulated by several chaperone proteins, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…The latter would be compatible with DNA microarrays revealing diminished expression of numerous heat shock proteins (chaperones) in HMGB1 −/− MEFs relative to the parental cells (Krynetskaia et al 2008), including Hsp90 mRNA as revealed by qRT-PCR (data not shown). Hsp90 protein has previously been shown to be an important factor in activation of telomerase (Holt et al 1999;Woo et al 2009). …”
Section: Discussionmentioning
confidence: 98%
“…The latter would be compatible with DNA microarrays revealing diminished expression of numerous heat shock proteins (chaperones) in HMGB1 −/− MEFs relative to the parental cells (Krynetskaia et al 2008), including Hsp90 mRNA as revealed by qRT-PCR (data not shown). Hsp90 protein has previously been shown to be an important factor in activation of telomerase (Holt et al 1999;Woo et al 2009). …”
Section: Discussionmentioning
confidence: 98%
“…The ER-specific isoform GRP94 is likewise phosphorylated by this kinase [97,98], raising again the logistical question of how an ER chaperone could possibly be modified by a cytosolic kinase. Although the exact biological function of these PTMs in human Hsp90 is still unclear, some authors have observed implications in apoptosome formation, arylhydrocarbon receptor-dependent transcriptional repression, BRaf/MKK/ERK signaling and telomerase activation [99][100][101][102]. In another report, Hsp90 was shown to enhance phosphorylation of eukaryotic initiation factor 2α, but only when the chaperone itself had been phosphorylated beforehand by CK2 [103].…”
Section: Phosphorylationmentioning
confidence: 95%
“…Overexpression of a truncated p23 corresponding to deltap23 leads to a decrease in hTERT levels and to down-regulation of telomerase activity (Woo et al 2009). …”
Section: Dna Damage Recognition/dna Repair/free Radicalsmentioning
confidence: 99%